Β-1, 3-Glucanases and chitinases participate in the stress-related defence mechanisms that are possibly connected with modulation of arabinogalactan proteins (AGP) required for the androgenesis initiation in rye (Secale cereale L.). (January 2021) - Zieliński, Kamil; Dubas, Ewa; Gerši, Zuzana; Krzewska, Monika; Janas, Agnieszka; Nowicka, Anna; Matušíková, Ildikó; Żur, Iwona; Sakuda, Shohei; Moravčíková, Jana
Graphical abstract: Highlights: Modulation of androgenesis-inducible stress intensity causes changes in the activity of the β-1, 3-glucanases, chitinases and AGP in rye. ∼26 kDa and some acidic isoforms of β-1, 3-glucanases are anther specific. β-1, 3-Glucanases and chitinases (GH18 and GH19) are highly active in anthers. JIM 4 and JIM 13 are detectable in anthers/microspores. JIM 13 is required to trigger microspores towards embryogenesis. Abstract: This work presents the biochemical, cytochemical and molecular studies on two groups of PR proteins, β-1, 3-glucanases and chitinases, and the arabinogalactan proteins (AGP) during the early stages of androgenesis induction in two breeding lines of rye ( Secale cereale L.) with different androgenic potential. The process of androgenesis was initiated by tillers pre-treatments with low temperature, mannitol and/or reduced glutathione and resulted in microspores reprogramming and formation of androgenic structures what was associated with high activity of β-1, 3-glucanases and chitinases. Some isoforms of β-1, 3-glucanases, namely several acidic isoforms of about 26 kDa; appeared to be anther specific. Chitinases were well represented but were less variable. RT-qPCR revealed that the cold-responsive chitinase genes Chit1 and Chit2 were expressed at a lower level in the microspores and whole anthers while the cold-responsive Glu2 and Glu3 were not active. The stress pre-treatments modifications promoted the AGP accumulation. An apparent dominance of some AGP epitopes (LM2, JIM4 and JIM14) was detected in the androgenesis-responsive rye line. An abundant JIM13 epitopes in the vesicles and inner cell walls of the microspores and in the cell walls of the anther cell layers appeared to be the most specific for embryogenesis.